Profiling Pencabulan Anak dibawah Umur: Tantangan dan Solusi dalam Melindungi Anak di Kecamatan Kota Bangun - Miranda, Tasya; Apriyanti, Rini; Erawaty, Rika (Dinasti Research, 2025)
Child molestation is a serious problem that demands special attention from various parties. This study examines profiling techniques as an investigative method in identifying the patterns and characteristics of child molesters in Kota Bangun Sub-district. Whether profiling techniques have the potential to assist law enforcement officials in identifying perpetrators more quickly and accurately. However, limited data, lack of experts, and lack of inter-agency coordination are obstacles in its application. In addition, the victim's fear of reporting and the community's low understanding of child protection rights are also obstacles in preventing and handling cases of sexual abuse. the research uses a descriptive Socio Legal approach and uses a qualitative approach. The types of data used are primary data and secondary data. Data collection techniques in this research use interview techniques and document studies. The data analysis technique uses qualitative data analysis. Based on the results of the research that has been conducted, recommends increasing the capacity of the apparatus in applying profiling techniques, strengthening the crime database system, and educating the public to increase awareness and courage to report. In addition, psychological rehabilitation services for victims need to be optimized to minimize long-term impacts. With a multidisciplinary approach and better coordination, it is hoped that efforts to prevent and handle child abuse can be carried out more effectively.